Are implicit emotion measurements evoked by food unrelated to liking?. (October 2015) - Mojet, Jozina; Dürrschmid, Klaus; Danner, Lukas; Jöchl, Max; Heiniö, Raija-Liisa; Holthuysen, Nancy; Köster, Egon
Abstract: In an effort to find a simple method to measure implicit and unconscious emotional effects of food consumption, a number of methods were compared in an experiment in which 3 groups of at least 24 subjects were each exposed to a pair of yoghurts of the same brand and marketed in the same way, but with different flavours or fat content. The methods used were eye tracking of the packaging, face reading during consumption, a new emotive projection test (EPT) and an autobiographical reaction time test based on mood congruency. In the emotive projection test the subjects rated photographs of others on 6 positive and 6 negative personality traits after having eaten the yoghurt. It showed clear differences in two of the three pairs of yoghurt. The autobiographical congruency test failed to reach significance although all findings went in the same direction as the ones in the EPT. Liking and familiarity with the products were also measured and the fact that they were not related to the emotional effects was established. Eye tracking showed effects of familiarity when the measurements before and after consumption of the yoghurts were compared. The results of the face reading test are not reported due to technical difficulties. Although liking itself was not correlated with the emotional effects in the emotive projection test, shifts in liking caused by consumption of the product did, indicating the emotional importance of pleasant surprise or disappointment in the confrontation between the expected and the actual experience of the product. Sensory differences in the fruit flavours had no effects on the emotional reactions, but change in fat content did, while vanilla flavour had a strong positive emotional effect. Highlights: Implicit emotional measurements can deliver product information that is not related to product liking. The emotional appreciation of other people can be changed by food consumption. Just like in unknowingly perceived ambient odours, vanilla flavour in yoghurt has positive mood effects.